Plotted, shot, and painted: cultural representations of biblical women - Exum, J. Cheryl (Classic reprints, 2012)
Plotted, Shot, and Painted stakes out new territory for feminist biblical criticism. It considers what happens to biblical women in popular culture, in art and in film, and it foregrounds questions about how gender interests affect interpretation and about the roles and responsibilities of commentators and readers. (back cover)